Osteopontin Promotes Trophoblast Invasion in the Smooth Muscle Cell-Endothelial Co-Culture At Least Via Targeting Integrin αvβ3. (15th October 2020) - Ke, Ru; Zheng, Liting; Zhao, Falan; Xia, Junxia
Preeclampsia is a pregnancy disorder, whereas the underlying mechanisms and etiological factors of this complication remain elusive. Studies have reported that decreased invasiveness of trophoblast cells, immunity disorder in the maternal–fetal interface, and oxidative stress may contribute to the development of preeclampsia. In the present study, we firstly co-cultured the smooth muscle cells (SMCs) and endothelial cells (ECs) to mimic the decidua and myometrium interface and examined the effects of osteopontin (OPN) on the invasive potential of trophoblasts in the SMC-EC co-culturing system. Our results showed that HTR-8/SVneo cells after hypoxia treatment showed enhanced invasive potential in the SMC-EC co-culturing system. OPN levels in the culture media from hypoxia-treated HTR-8/SVneo cells were significantly increased. More importantly, OPN treatment upregulated integrin, beta 3 and integrin, beta 5 expression in HTR-8/SVneo cells, and promoted HTR-8/SVneo cell invasion in the transwell invasion assay and SMC-EC co-culturing system. Mechanistically, treatment with integrin αvβ3 inhibitor significantly attenuated the enhanced invasive potential of HTR-8/SVneo cells treated with OPN in the SMC-EC co-culturing system. In conclusion, our study for the first time established the SMC-EC co-culturing system to examine the invasive potential of trophoblasts. Our results indicated that OPN promoted the invasive capacity of trophoblasts via at least targeting αvβ3 in the EC-SMC co-culturing system. Future studies were required to further validate the EC-SMC co-culturing system and to determine the molecular mechanisms of OPN-mediated trophoblast invasion.